2008
DOI: 10.1002/clen.200700086
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous Waste Pollution Prevention Using Clay with Admixtures

Abstract: Landfill is the most commonly used method for disposal of waste materials since it is one of the least expensive methods. In order to dispose of any hazardous material to a landfill, a liner is used, which protects the underlying land and groundwater since it acts as a barrier to fluid movement. Of the various methods available for providing improved and more effective properties of landfills, methods involving the use of bentonite, cement, lime, gypsum, etc., have been explored in the laboratory. The aim is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…Quest for new adsorbing material has directed several scientists to search for more efficient sorbent material for environmental remediation applications [15][16][17] for e.g. zeolites [4], ionic liquid [18], fly ash [19], rice husk [20], soil [21][22][23], clays [24][25][26][27][28][29][30][31], and composite materials [32,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quest for new adsorbing material has directed several scientists to search for more efficient sorbent material for environmental remediation applications [15][16][17] for e.g. zeolites [4], ionic liquid [18], fly ash [19], rice husk [20], soil [21][22][23], clays [24][25][26][27][28][29][30][31], and composite materials [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays the most promising way that is chiefly employed for the sorption of many organic and inorganic compounds in synthetic and industrial effluents is the use of naturally occurring clay minerals . Naturally occurring clay minerals are phyllosilicate groups.…”
Section: Introductionmentioning
confidence: 99%
“…These metals have commonly toxic effect on human's (and animal's) body and they cannot be decomposed to the safe materials. The main source of these metals is industrial sewage [2,3]. In countries with dry climate, home and industrial sewages can be used for irrigation of farms.…”
Section: Introductionmentioning
confidence: 99%
“…There have also been increasing interests of removing the harmful effects of different heavy metals, which are generally present in industrial waste. An experimental study to decrease the negative effects of metal ions by using bentonite, cement, lime, and gypsum was studied and the experimental system was modeled mathematically in 26. Zn(II) removal was examined by using tea factory waste from industrial leachate and demonstrated that Zn(II) adsorption on tea factory waste followed pseudo‐second‐order‐kinetics in 27.…”
Section: Introductionmentioning
confidence: 99%